Influence of Message Theme on Consumer Perceptions of Lab Grown Meat - Kellie Kubacak; Courtney Meyers; Hannah L Ford; Nan Li; Lindsay Kennedy (Journal of Applied Communications, 2022)
Lab grown meat is a new technology being developed as a potential alternative protein source. Although some research has been done about public perception of lab grown meat, no studies to date have observed the effects of message themes on public perception of lab grown meat. The study sought to better understand measures of uncertainty and risk and benefit perceptions after viewing a themed blog post about lab grown meat. Participants were randomly assigned one of three themed blog posts - against lab grown meat, neutral, or support lab grown meat. Perception questions were asked after viewing the blog post, and a total of 238 responses were collected. Results indicated the message theme had a statistically significant effect on risk perception, benefit perception, and intention to consume, but not on message evaluation or measures of uncertainty. Further discussion as well as suggestions for future research are included.
Keywords: Risk and benefit perceptions; Lab grown meat; Meltwater; Uncertainty perceptions